HUBUNGAN ANTARA NILAI RASIO NEUTROFIL-LIMFOSIT DENGAN TERJADINYA INFEKSI COVID-19 DI RUMAH SAKIT PUTRI HIJAU MEDAN PERIODE 2020 - Citra, Irwanto; Tambunan, Ronad T.H; Pakpahan, Edwin Anto (Universitas Methodist Indonesia, 2022)
Background: Patients with severe COVID-19 always have a high mortality rate, while inflammatory immunity to COVID-19 infection such as the Neutrophil-Lymphocyte Ratio (NLR) reflects the progress of the infection. It is used by clinicians as an early identification of high-risk patients or to determine the seriousness of the disease. This study aims to determine whether there is a relationship between the ratio value and COVID-19 infection. Objective: To find out whether there is a relationship between NLR values and COVID-19 infection. Method : The research design used was a cross-sectional observational analytic study. In this study using medical record data as much as 100. Result : A total of `100 medical record data of COVID-19 patients for the 2020 period were collected, of which the largest age group was 36-45 with 21 people (21.0%), and based on gender group where the number of men was 61 people (61.0%). However, in this study there was no relationship between an increase in RNL and COVID-19 (P = 0.504, PR = 1.138).